Grasping the stakeholder perspective: Understanding the messaging strategies of the barangay emergency networks health emergency and response system through the lens of stakeholder theory - Alban, Gabriel Alfonso G (Animo Repository, 2024)
Using Stakeholder Theory (Lewis, 2019), this study investigated the process in which messaging strategies are planned, communicated, and received by the stakeholders of the organization. The goal of the research is to answer the research question: “How does DRRM-Barangay Poblacion, Makati City utilize messaging strategies of BENHEARS (Barangay Emergency Networks Health Emergency and Response SYSTEM) to achieve stakeholders' uniformed understanding of the BENHEARS Project?”. The researchers conducted semi-structured interviews with 30 ‘definitive stakeholders’ described by the organization through the definition of Lewis (2019), which has been divided into three sectors of Persons with Disabilities (PWDs), Seniors, and Students. The responses were analyzed using thematic analysis to identify themes in Lewis’ (2019) definition and illustrate the messaging strategies utilized. The findings revealed diverse responses with the organization’s messaging strategies, and how it is perceived by the stakeholders. The researchers attributed these responses to comprehensive messaging, credibility messaging, community cooperation messaging, tailored messaging, and resolution messaging. Stakeholder Theory emerged as a vital tool for clarity and understanding, raising awareness, and aiding in resolution.